Association Between Physical Activity Level and Pelvic Floor Muscle Variables in Women - Carvalhais, Alice; Da Roza, Thuane; Vilela, Sofia; Jorge, Renato Natal; Bø, Kari (International Journal of Sports Medicine, 2018)
In order to investigate the potential impact of physical activity (PA) on pelvic floor muscle (PFM) function, a cross-sectional study was made to analyse the association between PA level and vaginal resting pressure (VRP) and PFM strength and endurance. Thirty-eight continent women and 20 women with stress urinary incontinence (SUI) aged 19 to 49 years were enrolled in the study. PFM variables were assessed by manometry. The PA level was assessed through the International Physical Activity Questionnaire – Short Form. The International Consultation on Incontinence Questionnaire-Urinary Incontinence – Short Form was applied to identify SUI. Pearson’s correlation coefficients were applied to estimate the association between PA and PFM variables. Incontinent women were classified as having a high PA level compared to the continent ones (65.0% vs 34.2%, respectively; p=0.030). There was a positive weak association between PA and VRP in continent (r=0.377) and an inverse association in incontinent women (r=−0.458). No associations were found between PA and PFM strength and endurance. Further studies are needed in order to identify a causal association between PA and SUI.
Keywords: endurance; pelvic floor muscles; physical activity level; strength; stress urinary incontinence; vaginal resting pressure